COMPARISON OF THE HAWALAH SYSTEM IN THE FIQH MUAMALAH AGAINST THE TURKEY’S MAJALLAH AL-AHKAM AND THE INDONESIAN CIVIL LAW - -, Fahriansah (JURNAL EKONOMI DAN BISNIS ISLAM, 2020)
This paper examines the system of debt transfer (hawalah) contained in the fiqh muamalah, then it is calculated against the hawalah system in the Majallah al-Ahkam al-Adliyah and the Civil Law of Indonesia. Because there are some differences between the three systems. This paper is conducted through a research study of litaration. The result of this study, if the system is in fiqh compared to the hawalah system contained in the Majallah Al-Ahkam Al-Adliyah, the author only found a slight change. However, when compared with Indonesian Civil Law, there are many changes ranging from the underwriting, the agreement, and the parties involved in the hawalah process.